Thermal shock resistant mullite brick and preparation method thereof

By introducing modified aluminum silicate composite particles, aluminum silicate ceramic fiber and nano graphene particles, and adopt a variety of pre -processing and process treatment methods, the traditional Molai stone brick is in high temperature and cold environment. The problem of cracking in China has significantly improved its heat shock resistance and high temperature resistance.

CN119330695AInactive Publication Date: 2025-01-21SHANDONG WEINAI ENERGY-SAVING MATERIALS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411864457.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-01-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional mullite bricks are prone to concentration of thermal stress in high-temperature, cold and fast-temperature environments, resulting in crack propagation or material failure, limiting their service life under frequent temperature fluctuations.

Method used

By introducing modified aluminosilicate composite particles, aluminum silicate ceramic fibers and nanographene particles into the mullite matrix material, and using processes such as plasma activation, ultrasonic dispersion, twin-screw mixing, vibration molding and step-by-step sintering. , significantly improving the thermal expansion matching and high temperature resistance of the material.

Benefits of technology

The thermal shock resistance of mullite bricks is significantly enhanced, suitable for industrial applications in high-temperature alternating environments, extending the service life of the product, and improving corrosion resistance and chemical attack resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of refractory materials, and discloses a thermal shock resistant mullite brick and a preparation method thereof, the thermal shock resistant mullite brick comprises the following raw materials by weight: 30-40 parts of a mullite matrix material; 15 to 20 parts of modified aluminosilicate composite particles; 8-12 parts of aluminum silicate ceramic fiber; 3 to 5 parts of nano graphene particles; 2 to 4 parts of a siloxane coating; the preparation method comprises the following steps: respectively pretreating the raw materials; mixing the pretreated mullite matrix material, modified aluminosilicate composite particles, aluminum silicate ceramic fibers and nano graphene particles, adding an aluminum phosphate solution with the mass fraction of 5%, and mixing by using a double-screw mixer to obtain slurry; injecting the mixed slurry into a mold, drying a molded green brick, and sintering after drying; and spraying a siloxane coating on the surface of the cooled green brick, and carrying out heat treatment to cure the coating to obtain the finished brick. The thermal shock resistance of the mullite brick is remarkably enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of refractory materials, in particular to a thermal shock resistant mullite brick and a preparation method thereof. Background Art

[0002] Thermal shock resistance refers to the ability of a material to resist cracks or structural damage caused by thermal stress when it is subjected to rapid temperature changes. For mullite bricks, good thermal shock resistance can not only extend their service life, but also ensure their structural stability in an environment with frequent temperature fluctuations, avoiding cracking, peeling or failure caused by thermal shock. Thermal shock resistance is particularly important in high-temperature scenarios such as blast furnace linings, hot blast furnaces, and regenerators that need to withstand rapid temperature changes.

[0003] Mullite material is widely used in the field of refractory materials due to its excellent high temperature performance, especially in industrial equipment such as high temperature furnace lining and hot blast furnace top cover, and has high use value. Its crystal phase structure enables it to show good high strength and corrosion resistance at high temperature.

[0004] However, due to the overall dense structure, traditional mullite bricks are prone to thermal stress concentration in high temperature and rapid cooling and heating environments, leading to crack expansion or material failure, limiting their service life under frequent temperature fluctuations. Therefore, it is particularly important to enhance the thermal shock resistance of mullite bricks. Summary of the invention

[0005] In view of this, the present invention proposes a thermal shock resistant mullite brick and a preparation method thereof, aiming to solve the problem of insufficient thermal shock resistance of mullite bricks in the current technology.

[0006] On the one hand, the present invention provides a thermal shock resistant mullite brick, comprising the following raw materials in parts by weight:

[0007] 30-40 parts of mullite matrix material with a particle size of 0.5mm<≤3mm;

[0008] 15-20 parts of modified aluminosilicate composite particles with a particle size of ≤50 μm;

[0009] 8-12 parts of aluminum silicate ceramic fiber;

[0010] 3-5 parts of nanographene particles;

[0011] 2-4 parts of silicone coating;

[0012] The physical and chemical indicators of the mullite matrix material are Al2O3: 60%-75%, SiO2: 25%-40%, Fe2O3 < 2%, and a bulk density of 2.9-3.1 g / cm 3 , porosity <5%;

[0013] The modified aluminosilicate composite particles are a composite of bauxite and silica-bauxite.

[0014] Optionally, the aluminum silicate ceramic fiber includes at least the following components in parts by weight:

[0015] 70-80 parts of silicon dioxide;

[0016] Alumina 15-25 parts;

[0017] Calcium oxide 1-5 parts;

[0018] 0.5-1 part of ferric oxide.

[0019] Optionally, the siloxane coating comprises at least the following components in weight fractions: 50-70 parts of polydimethylsiloxane, 10-20 parts of tetraethoxysilane, 10-20 parts of aluminum oxide, 5-10 parts of toluene, and 3-8 parts of other additives.

[0020] On the other hand, the present application also proposes a method for preparing thermal shock resistant mullite bricks, which is characterized by comprising the following steps:

[0021] Raw material pretreatment: mullite matrix material, modified aluminosilicate composite particles, aluminum silicate ceramic fibers, nanographene particles and siloxane coatings are respectively subjected to transformation and pretreatment;

[0022] Ingredient mixing: the pretreated mullite matrix material, modified aluminosilicate composite particles, aluminum silicate ceramic fibers and nanographene particles are mixed, and 5% by mass of aluminum phosphate solution is added, and mixed using a twin-screw mixer to obtain a slurry;

[0023] Molding and sintering: the mixed slurry is injected into the mold, the formed bricks are dried, and then sintered;

[0024] Coating curing: Spray a silicone coating on the surface of the cooled brick, and cure the coating by heat treatment to obtain a finished brick.

[0025] Optionally, the raw material pretreatment method includes:

[0026] Mullite matrix material:

[0027] The particles were subjected to plasma activation treatment, with a plasma power of 500 W and a treatment time of 10 minutes;

[0028] Modified aluminosilicate composite particles:

[0029] High-energy ball milling technology was used for uniform modification, and a layer of nano-alumina and nano-titanium oxide was coated on its surface, wherein the ball-to-material ratio was 3:1, the rotation speed was 400 rpm, and the time was 3 hours;

[0030] Aluminum silicate ceramic fiber:

[0031] The fibers were dispersed into the ethanol solution by ultrasonic dispersion method, with an ultrasonic power of 300 W, a frequency of 40 kHz, and a treatment time of 30 min;

[0032] Nanographene particles:

[0033] The reaction was stirred in dilute nitric acid for 2 hours, followed by centrifugation, washing, and drying;

[0034] Silicone coating:

[0035] Add a small amount of sodium silicate as a curing agent to the siloxane solution and let it stand for 24 hours.

[0036] Optionally, the speed of the twin-screw mixer during the mixing of the ingredients is 100 rpm and the time is 20 minutes.

[0037] Optionally, the molding and sintering further comprises, after the slurry is injected into the mold: eliminating bubbles by a vibration molding process, wherein the vibration frequency is 50 Hz and the vibration time is 10 minutes;

[0038] A static pressure of 50 MPa was applied to the mold during the molding process.

[0039] Optionally, the sintering in the forming and sintering is a step-by-step sintering, specifically:

[0040] The first heating rate is 5°C / min, the holding temperature is 800°C, and the holding time is 2 hours;

[0041] The secondary heating rate was 10°C / min, the final sintering temperature was 1600°C, and the holding time was 4 hours.

[0042] Optionally, argon gas is injected during the secondary heating during the step-by-step sintering process.

[0043] Optionally, the heat treatment for curing the coating is specifically: heat treatment at 250° C. for 2 hours.

[0044] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention proposes a thermal shock resistant mullite brick and a preparation method thereof, which significantly improves the thermal expansion matching and high temperature resistance of the material by introducing modified aluminum silicate composite particles, aluminum silicate ceramic fibers and nano-graphene particles into the mullite matrix material, thereby significantly enhancing the thermal shock resistance, and is suitable for industrial applications under high temperature alternating environments. The mullite matrix material is treated with plasma activation to improve the surface energy and bonding of the particles; the aluminum silicate composite particles are modified by high-energy ball milling to enhance the uniformity between particles and the interface bonding strength, and significantly improve the overall mechanical properties and stability of the brick body. The introduction of nano-graphene particles provides the brick body with excellent thermal conductivity, optimizes the thermal conduction behavior of the material, avoids the generation of local thermal stress, and further improves the thermal shock resistance. The coating adopts a siloxane composite material, which not only forms a dense protective film on the surface of the brick body, but also significantly improves the corrosion resistance and chemical erosion resistance of the brick body, and extends the service life of the product.

[0045] The preparation process uses pretreatment methods such as plasma treatment and ultrasonic dispersion to significantly improve the activity and uniformity of the raw materials; the twin-screw mixing process ensures the uniform distribution of the slurry, and the vibration molding process effectively removes bubbles and improves the density of the brick body; the step-by-step sintering process combined with argon injection technology further improves the density and organizational uniformity of the material during the sintering process. DETAILED DESCRIPTION

[0046] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] On the one hand, the present invention provides a thermal shock resistant mullite brick, comprising the following raw materials in parts by weight:

[0048] 30-40 parts of mullite matrix material with a particle size of 0.5mm<≤3mm;

[0049] 15-20 parts of modified aluminosilicate composite particles with a particle size of ≤50 μm;

[0050] 8-12 parts of aluminum silicate ceramic fiber;

[0051] 3-5 parts of nanographene particles;

[0052] 2-4 parts of silicone coating;

[0053] The physical and chemical indicators of the mullite matrix material are Al2O3: 60%-75%, SiO2: 25%-40%, Fe2O3 < 2%, and a bulk density of 2.9-3.1 g / cm 3 , porosity <5%;

[0054] The modified aluminosilicate composite particles are a composite of bauxite and silica-bauxite.

[0055] In this preferred embodiment, the aluminum silicate ceramic fiber comprises at least the following components in parts by weight: 70-80 parts of silicon dioxide, 15-25 parts of aluminum oxide, 1-5 parts of calcium oxide and 0.5-1 parts of ferric oxide.

[0056] In this preferred embodiment, the siloxane coating comprises at least the following components in weight fractions: 50-70 parts of polydimethylsiloxane, 10-20 parts of tetraethoxysilane, 10-20 parts of aluminum oxide, 5-10 parts of toluene, and 3-8 parts of other additives.

[0057] It can be understood that by introducing modified aluminosilicate composite particles, aluminum silicate ceramic fibers and nanographene particles into the mullite matrix material, the thermal expansion matching and high temperature resistance of the material are significantly improved, thereby significantly enhancing the thermal shock resistance.

[0058] On the other hand, the present application also proposes a method for preparing thermal shock resistant mullite bricks, which is characterized by comprising the following steps:

[0059] Raw material pretreatment: mullite matrix material, modified aluminosilicate composite particles, aluminum silicate ceramic fibers, nanographene particles and siloxane coatings are respectively subjected to transformation and pretreatment;

[0060] Ingredient mixing: the pretreated mullite matrix material, modified aluminosilicate composite particles, aluminum silicate ceramic fibers and nanographene particles are mixed, and 5% by mass of aluminum phosphate solution is added, and mixed using a twin-screw mixer to obtain a slurry;

[0061] Molding and sintering: the mixed slurry is injected into the mold, the formed bricks are dried, and then sintered;

[0062] Coating curing: Spray a silicone coating on the surface of the cooled brick, and cure the coating by heat treatment to obtain a finished brick.

[0063] In this preferred embodiment, the raw material pretreatment method comprises:

[0064] Mullite matrix material:

[0065] The particles were subjected to plasma activation treatment, with a plasma power of 500 W and a treatment time of 10 minutes;

[0066] Modified aluminosilicate composite particles:

[0067] High-energy ball milling technology was used for uniform modification, and a layer of nano-alumina and nano-titanium oxide was coated on its surface, wherein the ball-to-material ratio was 3:1, the rotation speed was 400 rpm, and the time was 3 hours;

[0068] Aluminum silicate ceramic fiber:

[0069] The fibers were dispersed into the ethanol solution by ultrasonic dispersion method, with an ultrasonic power of 300 W, a frequency of 40 kHz, and a treatment time of 30 min;

[0070] Nanographene particles:

[0071] The reaction was stirred in dilute nitric acid for 2 hours, followed by centrifugation, washing, and drying;

[0072] Silicone coating:

[0073] Add a small amount of sodium silicate as a curing agent to the siloxane solution and let it stand for 24 hours.

[0074] In this preferred embodiment, the speed of the twin-screw mixer during the mixing of the ingredients is 100 rpm and the mixing time is 20 minutes.

[0075] In this preferred embodiment, the molding and sintering further comprises, after the slurry is injected into the mold: eliminating bubbles by a vibration molding process, wherein the vibration frequency is 50 Hz and the vibration time is 10 minutes;

[0076] A static pressure of 50 MPa was applied to the mold during the molding process.

[0077] In this preferred embodiment, the sintering in the forming and sintering is a step-by-step sintering, specifically:

[0078] The first heating rate is 5°C / min, the holding temperature is 800°C, and the holding time is 2 hours;

[0079] The secondary heating rate was 10°C / min, the final sintering temperature was 1600°C, and the holding time was 4 hours.

[0080] It is understandable that the use of pretreatment methods such as plasma treatment and ultrasonic dispersion in the preparation process significantly improves the activity and uniformity of the raw materials; the twin-screw mixing process ensures the uniform distribution of the slurry, and the vibration molding process effectively removes bubbles and improves the density of the brick body; the step-by-step sintering process combined with argon injection technology further improves the density and organizational uniformity of the material during the sintering process.

[0081] In this preferred embodiment, the temperature is increased twice and argon is injected during the step-by-step sintering process.

[0082] In this preferred embodiment, the heat treatment for curing the coating is specifically: heat treatment at 250° C. for 2 hours.

[0083] Examples 1-4

[0084] The types, particle sizes and weight percentages of the raw materials of the thermal shock resistant mullite bricks of Examples 1-4 are shown in Table 1;

[0085] Table 1 Types, particle size specifications and weight percentages of raw materials in Examples 1-4

[0086]

[0087] According to the raw material formula in Table 1, the steps for firing thermal shock resistant mullite bricks are as follows:

[0088] Raw material pretreatment: mullite matrix material, modified aluminosilicate composite particles, aluminum silicate ceramic fibers, nanographene particles and siloxane coatings are respectively subjected to transformation and pretreatment;

[0089] Ingredient mixing: the pretreated mullite matrix material, modified aluminosilicate composite particles, aluminum silicate ceramic fibers and nanographene particles are mixed, and 5% by mass of aluminum phosphate solution is added, and mixed using a twin-screw mixer to obtain a slurry;

[0090] Molding and sintering: the mixed slurry is injected into the mold, the formed bricks are dried, and then sintered;

[0091] Coating curing: Spray a silicone coating on the surface of the cooled brick, and cure the coating by heat treatment to obtain a finished brick.

[0092] It should be pointed out that the weight proportions of the specific components of the aluminum silicate ceramic fiber and the siloxane coating in the above embodiments are shown in Table 2; among them, the other additives refer to methyltriethoxysilane (i.e., MTEOS, which enhances the adhesion between the coating and the substrate).

[0093] Table 2 Specific components of aluminum silicate ceramic fibers and siloxane coatings of Examples 1-4

[0094]

[0095] Comparative Example 1

[0096] The raw materials, particle sizes and weight percentages used in this comparative example are as follows:

[0097] 35 parts of mullite matrix material with a particle size of 0.1 mm < ≤ 0.5 mm;

[0098] 18 parts of modified aluminosilicate composite particles with a particle size of ≤50 μm;

[0099] 9 parts of aluminum silicate ceramic fiber;

[0100] 4 parts of nanographene particles;

[0101] The preparation method is as follows:

[0102] Raw material pretreatment: mullite matrix material, modified aluminosilicate composite particles, aluminum silicate ceramic fibers and nano-graphene particles are respectively modified and pretreated;

[0103] Ingredient mixing: the pretreated mullite matrix material, modified aluminosilicate composite particles, aluminum silicate ceramic fibers and nanographene particles are mixed, and 5% by mass of aluminum phosphate solution is added, and mixed using a twin-screw mixer to obtain a slurry;

[0104] Molding and sintering: The mixed slurry is injected into the mold, the molded bricks are dried, and then sintered.

[0105] It should be pointed out that the specific components of the aluminum silicate ceramic fiber are 74 parts by weight of silicon dioxide, 21 parts of aluminum oxide, 3 parts of calcium oxide, and 0.8 parts of iron oxide.

[0106] Table 3 is the test results of physical indicators of the products obtained in Examples 1-4 and Comparative Example 1

[0107]

[0108] It can be seen from Table 3 that the thermal shock resistant mullite brick prepared by the present invention has a porosity of ≤15.5%, a bulk density of ≥3.15, and has good thermal shock resistance.

[0109] In summary, the present invention proposes a thermal shock resistant mullite brick and a preparation method thereof, which significantly improves the thermal expansion matching and high temperature resistance of the material by introducing modified aluminum silicate composite particles, aluminum silicate ceramic fibers and nano-graphene particles into the mullite matrix material, thereby significantly enhancing the thermal shock resistance, and is suitable for industrial applications under high temperature alternating environments. The mullite matrix material is treated with plasma activation to improve the surface energy and bonding of the particles; the aluminum silicate composite particles are modified by high-energy ball milling to enhance the uniformity between the particles and the interface bonding strength, and significantly improve the overall mechanical properties and stability of the brick body. The introduction of nano-graphene particles provides the brick body with excellent thermal conductivity, optimizes the thermal conduction behavior of the material, avoids the generation of local thermal stress, and further improves the thermal shock resistance. The coating adopts a siloxane composite material, which not only forms a dense protective film on the surface of the brick body, but also significantly improves the corrosion resistance and chemical erosion resistance of the brick body, and extends the service life of the product.

[0110] The preparation process uses pretreatment methods such as plasma treatment and ultrasonic dispersion to significantly improve the activity and uniformity of the raw materials; the twin-screw mixing process ensures the uniform distribution of the slurry, and the vibration molding process effectively removes bubbles and improves the density of the brick body; the step-by-step sintering process combined with argon injection technology further improves the density and organizational uniformity of the material during the sintering process.

[0111] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A thermal shock resistant mullite brick, characterized in that: The invention comprises the following raw materials in parts by weight: 30-40 parts of mullite matrix material with a particle size of 0.5mm<≤3mm; 15-20 parts of modified aluminosilicate composite particles with a particle size of ≤50 μm; 8-12 parts of aluminum silicate ceramic fiber; 3-5 parts of nanographene particles; 2-4 parts of silicone coating; The physical and chemical indicators of the mullite matrix material are Al2O3: 60%-75%, SiO2: 25%-40%, Fe2O3 < 2%, and a bulk density of 2.9-3.1 g / cm 3 , porosity <5%; The modified aluminosilicate composite particles are a composite of bauxite and silica-bauxite.

2. The thermal shock resistant mullite brick according to claim 1, characterized in that: The aluminum silicate ceramic fiber comprises at least the following components in parts by weight: 70-80 parts of silicon dioxide; Alumina 15-25 parts; Calcium oxide 1-5 parts; 0.5-1 part of ferric oxide.

3. The thermal shock resistant mullite brick according to claim 2, characterized in that: The siloxane coating comprises at least the following components in weight fractions: 50-70 parts of polydimethylsiloxane, 10-20 parts of tetraethoxysilane, 10-20 parts of aluminum oxide, 5-10 parts of toluene, and 3-8 parts of other additives.

4. A method for preparing thermal shock resistant mullite bricks according to any one of claims 1 to 3, characterized in that: The following steps are involved: Raw material pretreatment: mullite matrix material, modified aluminosilicate composite particles, aluminum silicate ceramic fibers, nanographene particles and siloxane coatings are respectively subjected to transformation and pretreatment; Ingredient mixing: the pretreated mullite matrix material, modified aluminosilicate composite particles, aluminum silicate ceramic fibers and nanographene particles are mixed, and 5% by mass of aluminum phosphate solution is added, and mixed using a twin-screw mixer to obtain a slurry; Molding and sintering: The mixed slurry is injected into the mold, the formed bricks are dried, and then sintered; Coating curing: Spray a silicone coating on the surface of the cooled brick, and cure the coating by heat treatment to obtain a finished brick.

5. The method for preparing thermal shock resistant mullite bricks according to claim 4, characterized in that: The raw material pretreatment method comprises: Mullite matrix material: The particles were subjected to plasma activation treatment, with a plasma power of 500 W and a treatment time of 10 minutes; Modified aluminosilicate composite particles: High-energy ball milling technology was used for uniform modification, and a layer of nano-alumina and nano-titanium oxide was coated on its surface, wherein the ball-to-material ratio was 3:1, the rotation speed was 400 rpm, and the time was 3 hours; Aluminum silicate ceramic fiber: The fibers were dispersed into the ethanol solution by ultrasonic dispersion method, with an ultrasonic power of 300 W, a frequency of 40 kHz, and a treatment time of 30 minutes; Nanographene particles: The reaction was stirred in dilute nitric acid for 2 hours, followed by centrifugation, washing, and drying; Silicone coating: Add a small amount of sodium silicate as a curing agent to the siloxane solution and let it stand for 24 hours.

6. The method for preparing thermal shock resistant mullite bricks according to claim 5, characterized in that: The speed of the twin-screw mixer during the mixing of the ingredients is 100 rpm and the mixing time is 20 minutes.

7. The method for preparing thermal shock resistant mullite bricks according to claim 6, characterized in that: The molding and sintering process further includes, after the slurry is injected into the mold: eliminating bubbles by a vibration molding process, wherein the vibration frequency is 50 Hz and the vibration time is 10 minutes; A static pressure of 50 MPa was applied to the mold during the molding process.

8. The method for preparing thermal shock resistant mullite bricks according to claim 7, characterized in that: The sintering in the molding and sintering is a step-by-step sintering, specifically: The first heating rate is 5°C / min, the holding temperature is 800°C, and the holding time is 2 hours; The secondary heating rate was 10°C / min, the final sintering temperature was 1600°C, and the holding time was 4 hours.

9. The method for preparing thermal shock resistant mullite bricks according to claim 8, characterized in that: During the step-by-step sintering process, the temperature is raised twice and argon is injected.

10. The method for preparing thermal shock resistant mullite bricks according to claim 9, characterized in that: The heat treatment for curing the coating is specifically: heat treatment at 250° C. for 2 hours.

Citation Information

Patent Citations

  • Thermal-shock-resistant refractory brick and preparation method thereof

    CN106587960A

  • Polymethylsiloxane composite coating and preparation method thereof

    CN111944421A

  • High-temperature-resistant ceramic composite material as well as preparation method and application thereof

    CN113045301A

  • Method for applying a coating onto the surface of a mullite material, mullite material with a coating, and gas turbine component

    CN113874542A

  • Mullite composite brick as well as preparation method and application thereof

    CN118405930A